Strategic Business Risk Analysis of SAP Company - Ivanov, Ian; Rosecká, Nikola; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This master’s thesis presents a comprehensive strategic business risk analysis of SAP, focusing on its operations in the Czech Republic. The primary objective is to identify, assess, and prioritize strategic, financial, regulatory, operational, and technological risks that may affect SAP’s ability to achieve its strategic objectives for the period 2025–2028. The theoretical framework incorporates strategic management principles and risk analysis tools such as PEST analysis, Porter’s Five Forces, VRIO, and SWOT. The practical part applies these frameworks to SAP’s environment, followed by a semi-quantitative risk evaluation. Based on the identified critical risks, a strategic financial plan is developed and tested under various scenarios. A Monte Carlo simulation is then used to quantify the probability and impact of key uncertainties on the company’s financial objectives. The thesis concludes with strategic recommendations aimed at enhancing SAP’s resilience and long-term competitiveness in the Czech software market.
Vedoucí práce: Nikola Rosecká
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses